Risk of cognitive impairment in men with advanced prostate cancer treated with NHAs: A systematic review and network meta‐analysis - Shi‐Wei Huang; Li‐Chin Chen; Chi‐Shin Tseng; Chung‐Hsin Chen; Lun‐Hsiang Yuan; Wen‐Yi Shau; Yeong‐Shiau Pu (Wiley, 2023)
Abstract Novel hormonal agents (NHAs) have significantly improved outcomes in men with advanced prostate cancer. However, it remains unclear whether NHAs are associated with subsequent cognitive impairment. Thus, we sought to perform a network meta‐analysis to compare the risk of cognitive impairment across NHA types. Databases (PubMed, Embase, Scopus, and Web of Science), trial registries (Clinicaltrial.gov), the European Medicines Agency, and the US Food and Drug Administration drug safety reports were searched from inception through July 30, 2021. Eligible studies were clinical trials evaluating the risk of cognitive impairment between NHAs and placebo/standard care. Two independent investigators extracted the data and performed quality assessments using the Cochrane Risk of Bias Tool and ROBINS‐I. We estimated the risk ratios by the frequentist approach and calculated the ranking probabilities of all treatments with the surface under the cumulative ranking probabilities. The primary outcome and secondary outcome were odds ratio (OR) and incidence rate ratio of cognitive impairment, respectively. We identified 15 trials with 14,723 participants comparing HNAs with placebo/standard care. Treatments associated with cognitive impairment, from the most to the least, were enzalutamide (OR, 3.66; 95% confidence interval [CI], 2.84-4.73), apalutamide (OR, 1.76; 95% CI, 1.08-2.87), abiraterone acetate (OR, 1.64; 95% CI, 1.01-2.45), and darolutamide (OR, 1.11 95% CI, 0.51-2.39). After adjustment of treatment time duration, enzalutamide still had the highest risk of cognitive impairment with an incidence rate ratio of 2.17 (95% CI, 1.65-2.78). These findings suggest that NHAs, especially enzalutamide, may increase the risk of cognitive impairment compared with placebo/standard care.